From Policy to Practice: Islamic Religious Education Teachers' Sense-Making in Implementing the Merdeka Curriculum in Junior High Schools - Anis Rofi Hidayah; Durrotun Nafisah; Adam Mustakim; Mashudi; ST Mislihah; Saihan (Universitas Al-Amien Prenduan, 2026)
This study examines how Islamic Religious Education (PAI) teachers engage in sense-making when implementing the Merdeka Curriculum and Projek Penguatan Profil Pelajar Pancasila (P5) in junior high schools. Using sense-making theory as the analytical lens, this qualitative case study was conducted at SMP Negeri 2 Sukowono through interviews, observations, and document analysis involving PAI teachers and relevant school stakeholders. The data were analyzed interactively through data condensation, data display, and conclusion drawing. The findings identify a four-stage sense-making process: interpreting curriculum demands, contextualizing P5 themes through Islamic values and students' social realities, translating these interpretations into collaborative and reflective pedagogical practices, and evaluating students' understanding through authentic assessment. Rather than proposing an entirely new theoretical model, these stages provide an empirical adaptation and contextual elaboration of teacher sense-making theory within the implementation of the Merdeka Curriculum in Islamic Religious Education settings. Theoretically, this study contributes to the discourse on sense-making theory and curriculum interpretation by showing that teacher sense-making in Islamic education is contextual, collaborative, and transformative rather than merely administrative. Practically, the findings underscore the need to strengthen teacher collaboration, contextual curriculum interpretation, and institutional pedagogical support for PAI teachers implementing P5.